PERANCANGAN MUSIC VIDEO TENTANG PENTINGNYA KESADARAN ORANG TUA AKAN DAMPAK KEKERASAN TERHADAP ANAK MELALUI LAGU “A FORTIORI” BERBASIS ANIMASI 3D - Raphael Budi Pradipta; Bintang Pramudya Putra Prasetya; Sultan Arif Rahmadianto (Ma Chung Press, Universitas Ma Chung, 2026)
Parental violence in parenting patterns is one of the indicators of toxic parenting, which has the potential to disrupt a child’s healthy development. In addition to causing children to become withdrawn, toxic parenting may also lead to Borderline Personality Disorder (BPD), which can result in impulsive behavior in children. The song “A Fortiori” captures this phenomenon through a sequence of intense orchestral music. This study aims to provide “A Fortiori” with a medium that visually represents its implicit meaning to raise parental awareness of the impact of violence on children. The method used in this research is the Multimedia Development Life Cycle (MDLC) with a branching strategy design approach. The result of this study is a main medium in the form of a 3D animated music video with a semi-realistic style, accompanied by supporting media such as keychains, acrylic LED displays, poster designs, leaflets, stickers, vouchers, and a family photo as an iconic object featured in the music video. The distribution of this music video is expected to deliver a message to the public about the importance of parental awareness regarding the impact of violence on children through the song “A Fortiori.”